A method to represent subgrid‐scale updraft velocity in kilometer‐scale models: Implication for aerosol activation. Issue 7 (9th April 2014) - Malavelle, Florent F.; Haywood, Jim M.; Field, Paul R.; Hill, Adrian A.; Abel, Steven J.; Lock, Adrian P.; Shipway, Ben J.; McBeath, Kirsty
<x xml:space="preserve">Abstract</x> Updraft velocities strongly control the activation of aerosol particles or that component that act as cloud condensation nuclei (CCN). For kilometer‐scale models, vertical motions are partially resolved but the subgrid‐scale (SGS) contribution needs to be parametrized or constrained to properly represent the activation of CCNs. This study presents a method to estimate the missing SGS (or unresolved) contribution to vertical velocity variability in models with horizontal grid sizes up to ∼2 km. A framework based on Large Eddy Simulations (LES) and high‐resolution aircraft observations of stratocumulus and shallow cumulus clouds has been developed and applied to output from the United Kingdom Met Office Unified Model (UM) operating at kilometer‐scale resolutions in numerical weather prediction configuration. For a stratocumulus deck simulation, we show that the UM 1 km model underestimates significantly the variability of updraft velocity with an averaged cloud base standard deviation between 0.04 and 0.05 m s−1 compared to LES and aircraft estimates of 0.38 and 0.54 m s−1, respectively. Once the SGS variability is considered, the UM corrected averages are between 0.34 and 0.44 m s−1. Off‐line calculations of CCN‐activated fraction using an activation scheme have been performed to illustrate the implication of including the SGS vertical velocity. It suggests increased CCN‐activated fraction from 0.52 to 0.89 (respectively, 0.10 to 0.54) for a clean (respectively, polluted) aerosol environment for simulations with a 1 km horizontal grid size. Our results highlight the importance of representing the SGS vertical velocity in kilometer‐scale simulations of aerosol‐cloud interactions.